LEGAL PROTECTION OF COMMUNAL INTELLECTUAL PROPERTY IN INDONESIA - Ismail Koto; Ida Hanifah; Surya Perdana (Universitas Syiah Kuala, 2022)
Intellectual property protection contributes significantly to national and international economic development. Indonesia as a developing country must be able to take appropriate steps to anticipate all changes and developments as well as global trends so that national goals can be achieved. Protection for communal intellectual property is one way to reduce the practice of biopiracy, while ensuring fairness and equal treatment between owners and users of communal intellectual property. There are at least three important ways that must be considered: First, documentation of communal intellectual property is carried out through database development; Second, there is an obligation to fulfill the requirements for Communal intellectual property for which legal protection will be applied for, whether it has been in force or has been determined. Third, the owners of intellectual property rights, must show proof of approval for the use, distribution of ownership, or profit sharing from the owner of the communal intellectual property.